CCR2 Is Dispensable for Disease Resolution but Required for the Restoration of Leukocyte Homeostasis Upon Experimental Malaria-Associated Acute Respiratory Distress Syndrome - Pollenus, Emilie; Pham, Thao-Thy; Vandermosten, Leen; Robalo, Queeny; Possemiers, Hendrik; Knoops, Sofie; Opdenakker, Ghislain; Van den Steen, Philippe E. (Frontiers in Immunology, 2021)
Malaria complications are often lethal, despite efficient killing of Plasmodium parasites with antimalarial drugs. This indicates the need to study the resolution and healing mechanisms involved in the recovery from these complications. Plasmodium berghei NK65-infected C57BL/6 mice develop malaria-associated acute respiratory distress syndrome (MA-ARDS) at 8 days post infection. Antimalarial treatment was started on this day and resulted in the recovery, as measured by the disappearance of the signs of pathology, in >80% of the mice. Therefore, this optimized model represents an asset in the study of mechanisms and leukocyte populations involved in the resolution of MA-ARDS. C-C chemokine receptor type 2 (CCR2) knock-out mice were used to investigate the role of monocytes and macrophages, since these cells are described to play an important role during the resolution of other inflammatory diseases. CCR2 deficiency was associated with significantly lower numbers of inflammatory monocytes in the lungs during infection and resolution and abolished the increase in non-classical monocytes during resolution. Surprisingly, CCR2 was dispensable for the development and the resolution of MA-ARDS, since no effect of the CCR2 knock-out was observed on any of the disease parameters. In contrast, the reappearance of eosinophils and interstitial macrophages during resolution was mitigated in the lungs of CCR2 knock-out mice. In conclusion, CCR2 is required for re-establishing the homeostasis of pulmonary leukocytes during recovery. Furthermore, the resolution of malaria-induced lung pathology is mediated by unknown CCR2-independent mechanisms.